The judicial ruling amending the arbitrary conditions in the adhesion contract is a source of obligation - Bouaroudj, Khaoula; Boudeliou, Salim (Journal of Human Sciences, 2021)
The presence of arbitrary conditions in adhesion contracts adversely affects the weak party, which makes him in need of legal protection, and for this reason the Algerian legislator has intervened to address this situation, by granting the judge the authority to amend the arbitrary condition contained in the adhesion contract, and this amendment is considered to be a renewal of the obligation as the resulting commitment cancels about the contract and establishes a new commitment from the judicial ruling, and accordingly this study came to search for this judicial ruling as a source of commitment.